SuperTIGER instrument abundances of galactic cosmic rays for the charge interval 41 â©½ Z â‰¤ 56 - Walsh, Nathan Elliot; Akaike, Yosui; Binns, Walter Robert; Bose, Richard G.; Brandt, Terri J.; Braun, Dana L.; Cannady, Nicholas W.; Dowkontt, Paul F.; Hams, Thomas; Israel, Martin H.; Krizmanic, John F.; Labrador, Allan W.; et al. (Advances in Space Research, 2022)
We report preliminary elemental abundance results from the 55-day long-duration-balloon flight of SuperTIGER (Super Trans-Iron Galactic Element Recorder) during the 2012-2013 austral summer. SuperTIGER measured the relative abundances of Galactic cosmic-ray (GCR) nuclei with high statistical precision and well resolved individual element peaks from â‚â‚€Ne to â‚„â‚€Zr. SuperTIGER also made exploratory measurements of the relative abundances up to â‚…â‚†Ba. Although the statistics are low for elements heavier than â‚„â‚€Zr, we present, for the first time, relative abundance measurements of charges Z = 41-56 with individual element resolution. GCR measurements up to â‚„â‚€Zr support a source acceleration model where supernovae in OB associations preferentially accelerate refractory elements that are more readily embedded in interstellar dust grains than volatiles. In addition, injection into the GCR for both refractory and volatile elements appears to follow a charge dependence consistent with their grain sputtering cross sections. By extending the GCR measurement range past â‚„â‚€Zr, we can begin to further constrain these models. Â© 2022 COSPAR. Published by Elsevier. Received 1 November 2021, Revised 22 March 2022, Accepted 26 April 2022, Available online 10 May 2022. This research was supported by NASA under grants NNX09AC17G, NNX14AB25G, NNX15AC23G and 80NSSC20K0405, by the McDonnell Center for the Space Sciences at Washington University, and by the Peggy and Steve Fossett Foundation. We thank the NASA Columbia Scientific Balloon Facility, the NASA Balloon Program Office, and the NSF United States Antarctic Program for the excellent and highly professional efforts that resulted in two successful long-duration balloon flights for SuperTIGER. Accepted Version - 1-s2.0-S0273117722003404-main.pdf